Fun Math Melalui Media Dart Game Berbasis Model Kooperatif pada Siswa SMP Negeri 3 Kota Ternate - Muzakir Hi Sultan; Isman M Nur; Ruslan Laisouw; Hasanuddin Usman; Yani Awal; Fachmi Buamona; Maya Rumakat (Universitas Majalengka, 2026)
The cooperative learning model using the Dart Game media is a variation of learning derived from the Dart Board game, which can then be applied as a learning medium to improve students’ learning outcomes. The objectives of this activity are: (1) to determine the application of the Fun Math method on students’ interest in learning mathematics, and (2) to determine the effect of the Fun Math method in terms of enjoyment and the use of teaching aids on students’ interest in learning mathematics. The participants of this training and mentoring activity were 21 students from SMP Negeri 3 Kota Ternate. The results showed that: (1) The calculated t value of 2.710 > t table value of 1.72, or Sig value 0.01 < 0.05, so H₀ is rejected. It can be concluded that there is a significant effect of enjoyment on students’ learning interest. (2) The calculated t value of 6.434 > t table value of 1.72, or Sig value 0.04 < 0.05, so H₀ is rejected. It can be concluded that there is a significant effect of the use of teaching aids on students’ learning interest. (3) The calculated F value is 69.032, and with a significance level of α = 0.05, the F table value is 3.09. Since the calculated F value of 4.022 > F table value of 3.09 or Sig value 0.036 < 0.05, H₀ is rejected. It can be concluded that there is a simultaneous (combined) effect of enjoyment (X₁) and the use of teaching aids (X₂) on students’ learning interest. Through this community service activity, it is expected that the use of the Fun Math method through the Dart Game media, with the variables of enjoyment and the use of teaching aids, has a significant positive effect on students’ interest in learning.